The Politics of Education: Social Pressure and Political Influence in Arab Local Authorities - Rami SAFFURI (SEA: Practical Application of Science)
This article examines the appointment of education department directors in Arab local authorities in Israel, focusing on the influence of hamula (clan) politics. Drawing upon court hearings and verdicts, the study reveals that hamula politics significantly impact these appointments, leading to procedural irregularities, flexible interpretations of qualification requirements, and the prevalence of extraneous political considerations. The analysis highlights a disconnect between state regulations and local practices, driven by internal political pressures and familial ties. This research underscores the complex interplay between national policies, local governance, and traditional social structures within the Arab education system in Israel, demonstrating how hamula politics undermine merit-based appointments and perpetuate systemic challenges.